A novel approach to a two-stroke dual stage expansion engine concept - Srinivasa, Kiran Subrahmanya Banavathy; Shankaregowda, Prajwal Kagganagadde (My University, 2016)
The SICO engine concept was proposed by Per-Arne Sigurdsson. The engine comprises of two main cylinders for combustion implementing a two-stroke cycle operation and a single help cylinder running at twice the engine speed. At the end of combustion, the burned gases from the main cylinder are transferred to the help cylinder where the second stage expansion occurs simultaneously along with the main cylinder. The cylinders are considered to be thermally insulated and along with the parallel expansion cylinder aims to derive a higher engine efficiency. The charged induction of air is done by means of a compressor cylinder/radial compressor. The engine concept is evaluated for a power generation application where the engine efficiency at a single operating speed is essential. Consequently, the scavenging and friction models were augmented to better suit the model. Different aspects like the heat insulation, valve timings, cylinder dimensions, cylinder phasing, compression ratio of the main and help cylinders, charged induction using a radial compressor and compression cylinder were evaluated and optimized for the necessary application. Additionally, the SICO concept was compared with existing concepts that implement similar strategies such as the five-stroke engine concept that aims in utilizing exhaust energy for a four stroke cycle operation. The final SICO engine model is a 3.14L engine, producing a peak power of 81.5kW at 1500rpm. At this operating point the engine runs at an efficiency of 41.3%. Simulations show that the implementation of the help cylinder contributes to around a 7% brake efficiency increase and the effect of heat insulation is not of large significance for the break efficiency. Based on the preliminary evaluation of the concept by means of simulations, the engine efficiency of the concept is comparable to existing modern diesel engines and thus the SICO concept’s operation and implementation can be further pursued.
Keywords: Energi; Transport; Hållbar utveckling; Energiteknik; Energy; Transport; Sustainable Development; Energy Engineering